Evaluation of Mustard (Brassica spp.) Genotypes for Yield and Oil Content in Tandojam, Sindh, Pakistan - Vessar, Yasir Nawaz; Soomoro, Nighat Seema; Khan, Hajra; Baloch, Shahla Karim; Kaleri, Asif Ali; Tunio, Shahzad Ali (Indus Journal of Bioscience Research, 2025)
The evaluation of mustard (Brassica spp.) genotypes under specific agro-climatic conditions is essential to optimize productivity and oilseed quality. This study assessed the yield performance of ten mustard genotypes, including a commercial check variety, under the agro-climatic conditions of Tandojam, Sindh, Pakistan. The research was conducted at the Experimentation Station of the Oilseeds Research Institute, A.R.C. Tandojam, with the objective of identifying high-yielding genotypes suited for the region. Significant differences were observed among genotypes for seed yield and related traits. The commercial check variety, Mehran Raya, demonstrated superior yield performance with a plant height of 179.29 cm, 7.11 branches plant-1, 330.49 pods per plant, 20.63 seeds per pod, seed index of 4.92 g, a seed yield of 2086.70 kg ha-1 and an oil content of 35.35%. Notably, the genotype TJB-30 recorded the highest oil content at 37.83%, surpassing the check variety. The observed differences in yield and oil content were attributed to genetic diversity, environmental conditions, and cultivation practices. The findings highlight Mehran Raya's potential as a high-yielding mustard variety, suitable for cultivation in Tandojam, while TJB-30 shows promise for improving oil content. Mehran Raya exhibited superior yield, and TJB-30 demonstrated potential for enhanced oil quality. However, further research is necessary to assess their stability and adaptability across various environments, ensuring these genotypes' long-term suitability for sustainable oilseed production and contributing to regional food security. This study provides valuable insights for the selection of mustard genotypes tailored to the agro-climatic conditions of Tandojam, supporting efforts to enhance oilseed production in Pakistan.